Dampak Pendidikan Kewirausahaan Terhadap Intensi Kewirausahaan Melalui Mediasi Sikap dan Islamic Value pada Mahasiswa Agribisnis UMBandung - Tri Hanifawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The study's aim is to determine the impact of entrepreneurship education toward entrepreneurial intentions by combining entrepreneurial attitudes and Islamic values. Entrepreneurial intentions can be developed specifically through entrepreneurship education; however, it is thought to be influenced by indirect factors. The data were collected through a census of all students who had completed and passed a series of Business Development lectures in the Agribusiness Department in Universitas Muhammadiyah Bandung, then it was analyzed using SMART PLS and SPSS. The result shows that entrepreneurship education has a significant and positive impact on entrepreneurial attitude and Islamic value, however it is not direct significant effect to intentions. Then, the mediation variables analysis shows that entrepreneurial attitudes significantly and positively mediate the relationship between entrepreneurship education and entrepreneurial intentions. The study findings provide important recommendations to develop the entrepreneurship education curriculum of formal and non-formal education institutions.